Prognostic significance of HPV DNA and p16INK4a in anal cancer: a systematic review and meta-analysis - Urbute, Aivara; Rasmussen, Christina Louise; Belmonte, Federica; Obermüller, Theresa; Prigge, Elena-Sophie; Arbyn, Marc; Verdoodt, Freija; Kjaer, Susanne K. (Cancer epidemiology, biomarkers & prevention, 2020)
We conducted a systematic review and meta-analysis of observational studies evaluating survival in patients with anal cancer, according to human papillomavirus (HPV) DNA, p16INK4a, and combined HPV DNA/p16INK4a status. We systematically searched PubMed, EMBASE, and Cochrane Library databases to identify studies published in English until July 25, 2018, directly providing or allowing estimation of survival of patients with anal cancer according to the presence of HPV DNA and/or overexpression of p16INK4a. We estimated pooled HRs and 95% confidence intervals (CI) for overall survival (OS) using a random-effects model. We included 16 studies, comprising 1,724 patients with anal cancer tested for HPV DNA (65% positive), and 567 patients tested for p16INK4a (87% positive). The pooled HR for OS was 0.54 (95% CI, 0.33-0.89) for HPV DNA positive versus negative, 0.37 (95% CI, 0.24-0.57) for p16INK4a positive versus negative, and 0.36 (95% CI, 0.22-0.58) for HPV DNA positive/p16INK4a positive versus HPV DNA positive/p16INK4a negative patients with anal cancer. Patients with HPV DNA or p16INK4a positive anal cancer have significantly better OS compared with HPV DNA or p16INK4a negative. This points to the possible value of HPV DNA and/or p16INK4a testing when planning the management and follow-up strategy for patients diagnosed with anal cancer.